Grading practices and mindset development: the growth of both - Thiele, Julie (Kansas State University, 2016)
This study examined the impact grading policies have on students’ mindsets in urban Midwestern middle schools. The components of this quasi-experimental, causal comparative survey research relied on the grading policies in place at the school level and the students’ reporting of their mindset. Data was collected using a questionnaire containing eight Likert-type questions from the Implicit Theories of Intelligence scale (Dweck, 2006), as well as additional questions seeking the students’ perceptions of grading practices implemented in their buildings. Descriptive statistics, frequencies, t-tests and ANOVA tests were run measuring the impact that a variety of perceived grading practices had on students’ mindset levels. The findings from the research demonstrated no statistically significant differences between the mindset levels of students from schools with different grading policies. Further analysis revealed inconsistencies between student perceptions of the grading practices and the schools’ actual stated grading policies. It appears standards based and traditional grading practices, although specifically stated at the building level, appear to have blended together in the large school district, which may have led to the inconclusive results. Of significance was the finding that students perceived to understand the meaning of their grade, even if it is misaligned with the schools’ policy, reported a growth mindset in comparison to students that reported they did not understand their grade. These findings begin to explore the impact grading practices have on students, especially during the transition from traditional to standards based grading. Further research is needed to fully examine the transition between grading practices and students’ perceptions of those policies. When students’ perceptions of the standards based grading policy do not align with the actual policy, it is assumed that it will have no impact on students’ mindset levels. Future research would seek to understand ways in which educators making a transition from traditional to standards based grading can seek clarity of policies, seek accuracy of implementation and monitor students’ perceptions in alignment with the policies and practices.
Keywords: Mindset; Standards Based Grades; Grading Policies; Grading Practices; Middle Level Education